Physiological, histopathological and cellular immune effects of Pergularia tomentosa extract on Locusta migratoria nymphs - Meriam Miladi; Khemais Abdellaoui; Amel Ben Hamouda; Iteb Boughattas; Mouna Mhafdhi; Fatma Acheuk; Monia Ben Halima-Kamel (Journal of Integrative Agriculture, 2019)
The migratory locust Locusta migratoria (Orthoptera, Acrididae) is one of the most important pests due to its extensive and severe damage to crops in large parts of Africa and Asia. Biodegradable and ecologically natural products such as botanical insecticides are emerging candidates for replacement of usually applied chemical pesticides. The crude methanolic extract of Pergularia tomentosa (PME) was investigated for their toxicity and physiological aspects on L. migratoria nymphs. Results showed that treatment of newly emerged fourth and fifth instar nymphs resulted in significant mortality and significant repellent activity with an LC50 value of 0.18 and 0.38%, respectively, after seven days of treatment. The PME toxicity was also demonstrated by histopathological changes in the alimentary canal resulting in considerable disorganization and severe damage of the caeca and proventriculus structure. The extract induced cellular immune reactions which manifested by a significant decrease in the number of the differential haemocyte counts (prohemocytes and plasmatocytes) and important cell lysis. Data of biochemical analyses showed that the PME reduced the activity of acetylcholinesterase and induced the glutathione S-transferases. The neurotoxic effect was confirmed by the histological alterations in the brain structure, particularly in the neurosecretory cells showing typical signs of cell necrosis.